Roles of the Basic Helix-Loop-Helix Genes Hes1 and Hes5 in Expansion of Neural Stem Cells of the Developing Brain - Ohtsuka, Toshiyuki; Sakamoto, Masami; Guillemot, François; Kageyama, Ryoichiro (The Journal of biological chemistry, 2001)
Neural stem cells, which differentiate into neurons and glia, are present in the ventricular zone of the embryonal brain. The precise mechanism by which neural stem cells are maintained during embryogenesis remains to be determined. Here, we found that transient misexpression of the basic helix-loop-helix genes Hes1 and Hes5 keeps embryonal telencephalic cells undifferentiated although they have been shown to induce gliogenesis in the retina. These telencephalic cells later differentiate into neurons and astroglia when Hes expression is down-regulated, suggesting that Hes1- andHes5-expressing cells are maintained as neural stem cells during embryogenesis. Conversely, in the absence of Hes1and Hes5, neural stem cells are not properly maintained, generating fewer and smaller neurospheres than the wild type. These results indicate that Hes1 and Hes5 play an important role in the maintenance of neural stem cells but not in gliogenesis in the embryonal telencephalon.